Maternal PRDM10 activates essential genes for oocyte-to-embryo transition - Michelle K. Y. Seah; Brenda Y. Han; Yan Huang; Louise J. H. Rasmussen; Andrina J. Stäubli; Judith Bello-Rodríguez; Andrew Chi-Ho Chan; Maxime Gasnier; Heike Wollmann; Ernesto Guccione; Daniel M. Messerschmidt (Nature Communications)
Abstract PR/SET domain-containing (PRDM) proteins are metazoan-specific transcriptional regulators that play diverse roles in mammalian development and disease. Several members such as PRDM1, PRDM14 and PRDM9, have been implicated in germ cell specification and homoeostasis and are essential to fertility-related processes. Others, such as PRDM14, PRDM15 and PRDM10 play a role in early embryogenesis and embryonic stem cell maintenance. Here, we describe the first PRDM family member with a maternal effect. Absence of maternal Prdm10 results in catastrophic failure of oocyte-to-embryo transition and complete arrest at the 2-cell stage. We describe multiple defects in oocytes, zygotes and 2-cell stage embryos relating to the failure to accumulate PRDM10 target gene transcripts in the egg. Transcriptomic analysis and integration of genome-wide chromatin-binding data reveals new and essential PRDM10 targets, including the cytoskeletal protein encoding gene Septin11. We demonstrate that the failure to express maternal Septin11, in the absence of maternal PRDM10, disrupts Septin-complex assembly at the polar body extrusion site in MII oocytes. Our study sheds light into the essentiality of maternal PRDM10, the requirement of the maternal Septin-complex and the likely evolutionary conservation of this regulatory axis in human female germ cells.